Global Health Governance and Tropical Diseases - Till Bärnighausen; David E. Bloom; Salal Humair (Institute for the Study of Labor (IZA), 2013)
Global Health Governance (GHG) comprises the means adopted to promote decision making on actions to protect and promote global health, along with the underlying architecture of global health institutions, initiatives, and actors that facilitate these means. GHG is a key factor influencing health outcomes throughout the world. Over the past decade, the GHG system has increased dramatically in size and complexity. In the past half century, GHG has achieved successes against some tropical diseases, but going forward, it faces new challenges. The current GHG system has several weaknesses lack of participation, transparency, accountability, and efficiency but the system also has several strengths capacity for innovation, flexibility, and the ability to attract a motivated workforce and to encourage entrepreneurship. To adequately address tropical diseases in the future, GHG reforms will need to address some of the weaknesses while preserving the strengths.
Keywords: F35; F68; I18; 330; development assistance; tropical disease; global health governance; Gesundheitspolitik; Global Governance; Tropenkrankheit; Welt